Physical properties comparison of hydrogel from cassava starch using two different non toxic crosslinkers - Fitri Nur Kayati; Chandra Wahyu Purnomo; Yuni Kusumastuti; Rochmadi (Next Sustainability)
For the purpose of improving mechanical qualities, starch-based film hydrogel can be crosslinked. The choice of crosslinking agent is critical in adjusting hydrogel performance to fit the needs of specific applications. The present investigation examined the impact of two non-toxic crosslinking agents, namely citric acid and oxidized sucrose, on the mechanical and swelling properties of hydrogels. When compared to oxidized sucrose crosslinked hydrogels (OSH), citric acid crosslinked hydrogels (CAH) often offer a larger swelling; however, OSH without plasticizer is not included in this comparison. The OSH has the highest swelling value of 292% at pH 7, whereas the CAH has the highest swelling value of 116% at pH 7. Contrary to OSH film, which can only achieve 2.0 MPa, CAH film has a tensile strength of up to 3.75 MPa. Meanwhile, OSH film can achieve the greatest elongation of 54%.